Bacterial cell division: experimental and theoretical approaches to the divisome. (1st December 2015) - Broughton, Claire; Roper, David; van den Berg, Hugo; Rodger, Alison
Cell division is a key event in the bacterial life cycle. It involves constriction at the midcell, so that one cell can give rise to two daughter cells. This constriction is mediated by a ring composed of fibrous multimers of the protein FtsZ. However, a host of additional factors is involved in the formation and dynamics of this "Z-ring" and this complicated apparatus is collectively known as the "divisome". We review the literature, with an emphasis on mathematical modelling, and show how such theoretical efforts have helped experimentalists to make sense of the at times bewildering data, and plan further experiments.